Performance Analysis of Posyandu Cadres in the Wonorejo Health Center Work Area, Samarinda City - Irfansyah Baharuddin; Vanessa Julia Sonda (Window of Health : Jurnal Kesehatan, 2023)
The general goal of posyandu is to support the reduction of Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) in Indonesia through community empowerment efforts. Cadres are the implementers and main drivers of posyandu activities. Therefore, this research was conducted to determine the relationship between providing transport money, posyandu facilities, and cadre training and the performance of posyandu cadres. This type of research is analytical descriptive research with a cross-sectional approach. The respondents in this study were all posyandu cadres in the Wonorejo Community Health Center working area, namely 167 people from a population of 200 cadres from 2 sub-districts, namely Karang Anyar Subdistrict and Teluk Lerong Subdistrict. The research instrument used was a questionnaire tested for validity and reliability—data processing using SPSS by looking at the Chi-Square test results. The results of the research show that there is no relationship between the provision of transportation money (P value = 1.000), Posyandu facilities (P value = 0.051), and there is a relationship between cadre training (P value = 0.038) and the performance of Posyandu cadres in the Wonorejo Community Health Center working area. Suggestions for the posyandu development team (PKK, Puskesmas, Kelurahan) at regional and city levels are expected to increase the frequency of training. The Samarinda City Health Service, as well as the Teluk Lerong Village and Karang Anyar Village, will provide support and motivation so as to increase the work enthusiasm of cadres, and other researchers will continue research by adding other variables and using other research methods.